Knowledge of community around Dental Hospital of Faculty of Dentistry Universitas Padjadjaran (RSGM FKG Unpad) regarding street dentistry - Rif'ah, Lu'lu' Nikhlatur; Yubiliana, Gilang; Sutardjo, Dede (Universitas Padjadjaran, 2013)
The knowledge of society regarding “dental quack/street dentistry” can determine the individual’s behaviors in responding their existence Knowledge influenced by education, employment, age, interest, experience, culture, and source of information. The purpose of this study was to determine the knowledge of community around Dental Hospital of Faculty of Dentistry Universitas Padjadjaran regarding “dental quack/street dentistry”. This study was a descriptive study with survey techniques. Samples were taken by purposive sampling method with the sample size of 99 people. The result of this study showed that majority knowledge of the community was less than 40.40%. The conclusion of this study was the knowledge of community around Dental Hospital of Faculty of Dentistry Universitas Padjadjaran regarding “dental quack/street dentistry” was low.